THE RULE OF ST. BENEDICT SEBAGAI MODEL FORMASI SPIRITUAL SEMINARI - Benes, Meiliana Evita (Jurnal Amanat Agung, 2021)
Abstract: This research is based on the thought of a saint, St. Benedict, contained in a rule made in the context of monastery, the Rule of St. Benedict. This rule has shaped the spiritual life of God’s people for dozens of centuries. The strong emphasis on the balance of ora et labora, prayer and work, made this pattern relevant till date. This rule is also used as an approach to the forming of the patterns of spiritual formation in seminaries. Theological education is closely related to the growth of God’s people. Thus, seminary as one model of theological education needs to have a good pattern related to the spiritual formation of everyone in it. The condition of seminaries in the present era with a tendency to show more attention to academic formation than to spiritual formation can cause imbalance in the life of seminarians. The Rule of St. Benedict can be a reference model so that seminaries can carry out a balanced theological education process to ensure that the academic quality exists as a part of the wholistic spiritual life. Keywords: ora et labora, seminary, spiritual formation, the Rule of St. Benedict. Abstrak: Penelitian ini didasarkan oleh pemikiran seorang kudus, St. Benediktus yang tertuang dalam sebuah aturan yang dibuat dalam konteks biara, the Rule of St. Benedict. Aturan ini telah membentuk kehidupan spiritual umat Tuhan selama belasan abad. Penekanan yang kuat pada keseimbangan ora et labora, berdoa dan bekerja, membuat pola ini dapat digunakan hingga saat ini. Aturan ini juga digunakan sebagai pendekatan untuk membentuk pola formasi spiritual di seminari. Pendidikan teologi memiliki kaitan yang erat dengan pertumbuhan umat Tuhan. Dengan demikian, seminari sebagai salah satu model dari pendidikan teologi perlu memiliki sebuah pola yang baik terkait dengan formasi spiritual setiap orang di dalamnya. Kondisi seminari pada masa kini yang menunjukkan kecenderungan perhatian pada formasi akademik daripada formasi spiritual dapat mengakibatkan ketidakseimbangan dalam kehidupan para seminaris. The Rule of St. Benedict dapat menjadi sebuah model acuan agar seminari dapat menjalankan proses pendidikan teologi secara seimbang guna memastikan bahwa kualitas akademik hadir sebagai bagian dalam kehidupan spiritual secara holistik. Kata-kata kunci: ora et labora, seminari, formasi spiritual, The Rule of St. Benedict.